2018
DOI: 10.2147/tcrm.s155753
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width and the risk of being in poor glycemic control among patients with established type 2 diabetes

Abstract: BackgroundThe red cell distribution width (RDW) has been shown to be associated with the incidence and complications of type 2 diabetes (T2D). However, the relevance of RDW with the risk of being in poor glycemic control among patients with established T2D is largely overlooked.MethodsA total of 702 T2D participants from the REACTION study were enrolled in this study. Blood routine index, fasting plasma glucose, hemoglobin A1c and lipid profile data were available for all of the enrolled population.ResultsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 40 publications
4
25
1
Order By: Relevance
“…These results are similar to our study. Another study done by Yin et al (2018) revealed a noteworthy association between RDW and the risk of being in poor glycemic control among Type 2 diabetes mellitus subjects, which is on par with the results of our study. Chowta et al (2013) studied the hemogram pro ile of 2 groups of elderly diabetics < 60 years &> 60 years and found that the RDW of patients > 60 years had a higher value than the younger group which was statistically signi icant ( p-value 0.002 )which can be correlated with our study.…”
Section: Figure 3: Distribution Of the Study Population By Age And Hba1csupporting
confidence: 91%
“…These results are similar to our study. Another study done by Yin et al (2018) revealed a noteworthy association between RDW and the risk of being in poor glycemic control among Type 2 diabetes mellitus subjects, which is on par with the results of our study. Chowta et al (2013) studied the hemogram pro ile of 2 groups of elderly diabetics < 60 years &> 60 years and found that the RDW of patients > 60 years had a higher value than the younger group which was statistically signi icant ( p-value 0.002 )which can be correlated with our study.…”
Section: Figure 3: Distribution Of the Study Population By Age And Hba1csupporting
confidence: 91%
“…Measurements and definitions of smoking, drinking, obesity, and hypertension were as described previously. 3 The eGFR was estimated based on serum creatinine using the equation derived from the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI). 4 The primary outcome was rapid decline in eGFR, which defined as a decline in eGFR of >3 mL/min per 1.73 m 2 per year.…”
Section: Methodsmentioning
confidence: 99%
“…Red blood cell distribution width (RDW) is a hematological parameter, which reflects the heterogeneity of erythro-cyte volume, and it is traditionally used, along with the mean corpuscular volume, to tell the subtypes of anemia [5]. In recent years, several studies had assessed the possible association between RDW and diabetes [6][7][8][9][10][11]. However, studies in diabetic population generated inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…One cross-sectional study reported a significantly positive association between RDW and glycated hemoglobin A1c (HbA1c), independent of fasting blood glucose (FBG) levels in nondiabetic American adults [6] while the other reported a negative correlation between RDW and fasting glucose in elderly Chinese [7]. RDW was significantly higher in diabetic patients than healthy subjects and particularly higher in uncontrolled glycemia in a retrospective case-control study [8] while the other one [9] found that type 2 diabetes patients with higher RDW had significantly lower risk of poor glycemic control. The results of cohort studies were also inconsistent [10,11], due to sample size and the level of adjustment.…”
Section: Introductionmentioning
confidence: 99%